Oligomerization and Ca2+/calmodulin control binding of the ER Ca2+-sensors STIM1 and STIM2 to plasma membrane lipids - Bhardwaj, Rajesh; Müller, Hans-Michael; Nickel, Walter; Seedorf, Matthias (Bioscience reports, 2013)
Ca2+ (calcium) homoeostasis and signalling rely on physical contacts between Ca2+ sensors in the ER (endoplasmic reticulum) and Ca2+ channels in the PM (plasma membrane). STIM1 (stromal interaction molecule 1) and STIM2 Ca2+ sensors oligomerize upon Ca2+ depletion in the ER lumen, contact phosphoinositides at the PM via their cytosolic lysine (K)-rich domains, and activate Ca2+ channels. Differential sensitivities of STIM1 and STIM2 towards ER luminal Ca2+ have been studied but responses towards elevated cytosolic Ca2+ concentration and the mechanism of lipid binding remain unclear. We found that tetramerization of the STIM1 K-rich domain is necessary for efficient binding to PI(4,5)P2-containing PM-like liposomes consistent with an oligomerization-driven STIM1 activation. In contrast, dimerization of STIM2 K-rich domain was sufficient for lipid binding. Furthermore, the K-rich domain of STIM2, but not of STIM1, forms an amphipathic α-helix. These distinct features of the STIM2 K-rich domain cause an increased affinity for PI(4,5)P2, consistent with the lower activation threshold of STIM2 and a function as regulator of basal Ca2+ levels. Concomitant with higher affinity for PM lipids, binding of CaM (calmodulin) inhibited the interaction of the STIM2 K-rich domain with liposomes in a Ca2+ and PI(4,5)P2 concentration-dependent manner. Therefore we suggest that elevated cytosolic Ca2+ concentration down-regulates STIM2-mediated ER-PM contacts via CaM binding.
Im Titel ist "2+" hochgestellt
Gesehen am 25.11.2020